Development of Technopreneurship Learning Model in Vocational High School Machinery Program - Ismail, Edy; Samsudi, Samsudi; Widjanarko, Dwi (Journal of Vocational and Career Education, 2017)
This research aims to develop Technopreneurship learning model in package engineering expertise machining; test the effectiveness and practicality of the Technopreneurship learning model in package engineering expertise machining. The methods used are research and development. Subjects trials one Technopreneurship learning group. Instruments of colecting data are teacher and student’s questionnaire sheets, validation instruments, interpersonal, intrapersonal, skill observation sheet, product result, teachers and students response, cognitive test. Analysis of data with t test for effectiveness and practicality of learning. Results of the research is a Technopreneurship learning model that has 4 stages to improve attitudes technopreneur, develop products based on the results of an investigation into the need for appropriate technology tools in surrounding communities. Technopreneurship learning model effectively declared the results of post test better assessment of the results of pre-test assessment. Technopreneurship learning model implemented in the second semesters of grade XI who have taken industrial practice. Teachers must have a productive capabilities and entrepreneurship.